El verdugo = [videorecording (DVD)] : Executioner - Berlanga, Luis García; Manfredi, Nino, 1921-2004; Penella, Emma, 1930-; Isbert, José, 1885-1966 (Criterion collection, 2016)
A macabre farce about an undertaker who marries an executioner's daughter and reluctantly takes over her father's job so the family can keep their government allotted apartment.